Treatment of cervical cancer. Early stages. - Arana Arana, Julio (2015)
It is also understood with the names of intraepithelial carcinoma or pre-invasive carcinoma, and is defined as an injury involving the entire thickness of the squamous columnar epithelium of the cervix, which is replaced by cells microscopically they can not be distinguished from malignant carcinoma cells infiltrating. Throughout the epithelium there is a complete lack of normal stratification and loss of their own cellular characteristics of normal epithelium.